Adaptation of the Mullen Scales of Early Learning for use among infants aged 5‐ to 24‐months in rural Gambia. Issue 5 (10th March 2019) - Milosavljevic, Bosiljka; Vellekoop, Perijne; Maris, Helen; Halliday, Drew; Drammeh, Saikou; Sanyang, Lamin; Darboe, Momodou K.; Elwell, Clare; Moore, Sophie E.; Lloyd‐Fox, Sarah
Abstract: Infants in low‐resource settings are at heightened risk for compromised cognitive development due to a multitude of environmental insults in their surroundings. However, the onset of adverse outcomes and trajectory of cognitive development in these settings is not well understood. The aims of the present study were to adapt the Mullen Scales of Early Learning (MSEL) for use with infants in a rural area of The Gambia, to examine cognitive development in the first 24‐months of life and to assess the association between cognitive performance and physical growth. In Phase 1 of this study, the adapted MSEL was tested on 52 infants aged 9‐ to 24‐months (some of whom were tested longitudinally at two time points). Further optimization and training were undertaken and Phase 2 of the study was conducted, where the original measures were administered to 119 newly recruited infants aged 5‐ to 24‐months. Infant length, weight and head circumference were measured concurrently in both phases. Participants from both phases were split into age categories of 5–9 m ( N = 32), 10–14 m ( N = 92), 15–19 m ( N = 53) and 20–24 m ( N = 43) and performance was compared across age groups. From the ages of 10–14 m, Gambian infants obtained lower MSEL scores than US norms. Performance decreased with age and was lowest in the 20–24 m old group. Differential onsets of reduced performance were observed in the individual MSEL domains, with declines in visual perception and motor performance detected as early as at 10–14 months, while reduced language scores became evident after 15–19 months of age. Performance on the MSEL was significantly associated with measures of growth. Abstract : The Mullen Scales of Early Learning were adapted to assess cognitive development among infants aged 5‐ to 25‐ months in a rural area of The Gambia. From the age of 10‐14 months, Gambian infants had lower scores compared to US norms and the discrepancy in scores increased with age. Cognitive performance was also associated with the infants' height and weight.